2010
DOI: 10.1038/nn.2562
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptors mediate local anti-nociceptive effects of acupuncture

Abstract: Acupuncture is an invasive procedure commonly used to relieve pain. Acupuncture is practiced worldwide, despite difficulties in reconciling its principles with evidence-based medicine. We found that adenosine, a neuromodulator with anti-nociceptive properties, was released during acupuncture in mice and that its anti-nociceptive actions required adenosine A1 receptor expression. Direct injection of an adenosine A1 receptor agonist replicated the analgesic effect of acupuncture. Inhibition of enzymes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
609
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 712 publications
(638 citation statements)
references
References 46 publications
20
609
0
9
Order By: Relevance
“…This underscores the importance of local mechanisms such as the release of neuromodulators at the needling site [14] and spinal mechanisms such as segmental inhibition [11]. It is supposed, that activation of A-fiber afferents results in the activation of spinal inhibitory interneurons, those achieving primary analgesia within the same segment [124,125].…”
Section: Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…This underscores the importance of local mechanisms such as the release of neuromodulators at the needling site [14] and spinal mechanisms such as segmental inhibition [11]. It is supposed, that activation of A-fiber afferents results in the activation of spinal inhibitory interneurons, those achieving primary analgesia within the same segment [124,125].…”
Section: Results Interpretationmentioning
confidence: 99%
“…It is postulated that in response to the needle stimulation mechanisms of the endogenous pain modulation such as diffuse noxious inhibitory controls (DNIC), segmental inhibition, and descending pain control pathways lead to a decrease in pain perception [10,11]. At this, various centrally and/or peripherally acting neuromodulators and neurotransmitters such as endorphins [12], serotonin [13], ATP [14], etc. have been identified to play an important role in the analgesic effect of acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture is thought to stimulate inhibitory nerve fibers for a short period, reducing transmission of pain signal to the brain [33]. Acupuncture treatment activates endogenous analgesic mechanisms [34], causing secretion of endorphin which is an endogenous opioid [35] and triggering release of adenosine [36], producing a rapidly effective analgesic action on radicular sciatica. Extensive research has shown that acupuncture analgesia may be initiated by stimulation of high-threshold, small-diameter nerves in the muscles [37].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Goldman et al (2010) found that localized A 1 R activation underlies the antinociceptive effects of acupuncture. Manual stimulation of acupuncture needles resulted in localized extracellular increases in nucleotides (ATP, ADP, and AMP) and adenosine.…”
Section: Emerging Roles For Ectonucleotidases In Pain-sensing Neuronsmentioning
confidence: 95%